Jean-Louis Flandrin and Massimo Montanari (eds.), English edition by Albert Sonnenfeld: Food: A Culinary History - Davidson, Alan (Petits Propos Culinaires, 2024)
Jean-Louis Flandrin and Massimo Montanari (eds.), English edition by Albert Sonnenfeld: Food: A Culinary History: Penguin Books, New York, 2000: ISBN 0-14-029658-1: 592 pp., b&w photos, p/b, 18.